On-site detection of equid alphaherpesvirus 3 in perineal and genital swabs of mares and stallions - Vissani, Maria Aldana; Tordoya, Maria Silvia; Tsai, Yun-Long; Lee, Pei-Yu Alison; Shen, Yu-Han; Lee, Fu-Chun; Wang, Hwa-Tang Thomas; Parreño, Viviana; Barrandeguy, Maria Edith (Elsevier, 2019)
Equine coital exanthema (ECE) is an infectious, venereally transmitted muco-cutaneous disease affecting mares and stallions, caused by equid alphaherpesvirus 3 (EHV3). Diagnostic tools for rapid identification of EHV3 are of primary importance to diminish the risk of EHV3 dissemination at the time of breeding. In the last years, it has been shown that the performance of the insulated-isothermal polymerase chain reaction (iiPCR) is comparable to virus isolation, nested PCR and real-time PCR (qPCR) in detecting pathogens of various animal species. Analytical sensitivity and specificity of the iiPCR were compared with a qPCR, using a plasmid containing the target region of the EHV3 glycoprotein G gene and an Argentinian EHV3 isolate (E/9283/07 C3A). In order to evaluate the diagnostic performance of the iiPCR, nucleic acids of 85 perineal and genital swabs (PGS) of mares and stallions were extracted by tacoTM mini and tested by both techniques. EHV3 was detected in 46 and 45 of the 85 PGS by the iiPCR and qPCR, respectively. There was almost perfect agreement between the two diagnostic methods (98.82%; 95% CI: 95.03–100%; κ = 0.98). The iiPCR had a limit of detection of 95.00% at 6 genome equivalents per reaction and a detection endpoint for viral DNA comparable to that of the qPCR, and did not react with six non-targeted equine pathogens. The iiPCR represents a sensitive and specific method for the rapid on-site diagnosis of EHV3 infection. Its routinely implementation in breeding facilities, and artificial insemination and embryo transfer centers, will contribute to prevent the dissemination of this venereal, highly contagious disease in horses.